Prototype of a myoelectric prosthesis for the emulation of an elbow joint - Contreras, D.; Ramírez - García, A.; Gallegos, F.; Bazán, I (Revista Mexicana de Ingenieria Biomedica, 2015)
In this paper the development of a prototype for a myoelectric prosthesis elbow joint is described. It is divided into three parts; the first is the conditioning of the myoelectric signal (SME) which proposed a circuit that is formed by a stage of pre-amplification, followed by a stage of filtering, another stage of amplification and finally a stage of rectification. This circuit complies with the specifications for the detection of the SME according to the state of the art. The second part is the processing of the SME based on the method TKEO, this was implemented in MatLAB (MathWorks - Natick, Massachusetts, USA) in order to detect if the muscle is active or not, and proved to be robust and efficient. The third part focuses on the design and realization of the prototype, in the system of transmission was used a couple of gears and for the system of actuation were electrical actuators; both were defined considering several criteria referred to in this work. Finally, the three parts were joined for the emulation of flexion and extension movements of the prototype, using the microprocessor (Arduino UNO) and control module (controller servo Pololu 1350).